Reconfiguring a theological-spiritual vocabulary about death: Mysticism, “magic” and the case of Harry Potter and Albus Dumbledore - T. van Wyk (Acta Theologica)
Even to the most casual reader, J.K. Rowling’s overarching story about the “Boy who lived” is about death. Since the publication of the first book of the Harry Potter series in 1997, theologians and scholars of philosophy of religion have explored this theme within the story, as well as other eschatological related themes in the series. This article explores the topic of death in the Harry Potter series within the fields of Christian spirituality and eschatology and builds on previous research in this regard. The article focuses on the nature of Christian religious language about death, using Evelyn Underhill’s approach to mysticism and Jurgen Moltmann’s “personal eschatology”. The purpose is to indicate how the approaches to death of two main characters – Harry Potter and Albus Dumbledore – could contribute to a theological-spiritual vocabulary about death, and therefore to a Christian eschatology.